PENGARUH GAYA BELAJAR DAN WAKTU BELAJAR SISWA DI LUAR KELAS TERHADAP PRESTASI BAHASA INGGRIS DI SMP SE- KABUPATEN TULANG BAWANG - Hery Yufrizal (Aksara: Jurnal Bahasa dan Sastra, 2017)
The study aims at finding out the influence of students learning styles and their time to learn English outside classroom on the students English achievement at junior high schools of Tulang Bawang Regency in Lampung Province. The number students recruited as the sample for the study was 1038 and the number of teachers recruited as the sample was 70 teachers. The data for students learning styles were gained through a questionnaire which resulting students learning style categories of: a) communicative, b) concrete, authority-oriented, d) analytic, and e). undecided. For students time learning outside classroom was gained through a questionnaire resulting students who learn: a) less than an hour a day, b) 1-2 hours a day, c) 2-3 hours a day, d) 3-4 hours a day and e) more than four hours a day. The results show that there is no significant influence of students learning styles on their achievement of English subject. Students spending time learning English outside classroom has a significant effect on their English achievement. The average score of students who spent more than four hours a day had the highest score, followed by students who spent 2-3 hours a day. The lowest score was gained by the students who spent less than one hour a day learning English outside classroom.Key word: learning styles, time spent learning English outside classroom, English achievement